Autonomy and equal right to divorce with specific reference to Shi'i Figh and the Iranian legal system - Ghari Seyed-Fatemi, Seyed Mohammad (Islam and Christian-Muslim relations, 2006)
In this article I argue for the equal right of both spouses to divorce, since moral autonomy as embodied in the right to self-determination calls for this. The powerful moral demand of the contemporary human rights discourse has left no choice for Western countries but to allow divorce to be granted when the parties consent. The same factor has pushed many Muslims, including Iranians, to reform their system in favour of women. The problem for Shi'ites, unlike Christians, was not the denial of the right to divorce to both parties, but rather the unilateral privilege of the husband. Their reform was thus to direct the system toward an egalitarian position rather than to establish permissibility. Yet, the compelling factor for both was the same, that is, the appeal to individual autonomy and the right to self-determination. We will see that moral reinterpretation of the Islamic sources can offer an egalitarian right to divorce without diluting fundamental qur'anic teachings. An essential prerequisite for such an achievement is a methodological shift from literalistic interpretation of the qur'anic teachings and authentic sunna to the moral spirit of the textual sources.